2019
DOI: 10.1007/s41230-019-8169-8
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-resistant inorganic binder for sand core making in foundry practice

Abstract: The performance of sand core was improved by using the modified water glass as a binder and adding powder additives in the sand hardening process. The optimal proportion of the compound additives was determined by an orthogonal test, with a ratio of microsilica: polyvinyl alcohol solution: borax: B agent = 25: 20: 2: 1. The binder accounted for 2% of the sand by weight, and the compound additives accounted for 0.96%. The core box was heated to 175 °C, and the compressed hot air of 120 °C kept blowing for 40 s.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Compared to earlier product generations, the newest inorganic binder offers an improved humidity resistance, as stated by several research studies. 23,28,43 Specific additives, added to enhance the humidity resistance of cores, enable reaching up to 5 days of storage at 30°C and 70 % relative humidity without any significant impairment of strength. The literature and present findings revealed that inorganic cores exhibit a greater tendency to moisture absorption, as confirmed by the greater HL values resulting from the moisture absorption comparative tests conducted through the climatic chamber.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to earlier product generations, the newest inorganic binder offers an improved humidity resistance, as stated by several research studies. 23,28,43 Specific additives, added to enhance the humidity resistance of cores, enable reaching up to 5 days of storage at 30°C and 70 % relative humidity without any significant impairment of strength. The literature and present findings revealed that inorganic cores exhibit a greater tendency to moisture absorption, as confirmed by the greater HL values resulting from the moisture absorption comparative tests conducted through the climatic chamber.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proved that additives enhanced the bending strength and long-term stability of cores. 28,44 In addition, it should be pointed out that the storage stability of inorganic cores can be considerably extended by some logistical/practical techniques, such as air-conditioning the core storage areas within the foundry or reducing the core storage time by employing line production. In this regard, this study reveals that long storage in the foundry warehouse, up to 14 days (at 18°C and 32 % relative humidity), does not compromise the tolerances of inorganic cores, as demonstrated by the optical 3D analysis of surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another proposed solution was the utilization of additives that reduce the number of hydrophilic groups within the binder. Sond et al identified that adding micro silica, polyvinyl alcohol solution, borax, and an agent called B agent in the ratio of 25: 20: 2: 1 increased the tensile strength more than four times (1.19 MPa vs 0.27 MPa) when tested after 4 hours in 90% relative humidity [13,14].…”
Section: Moisture Resistancementioning
confidence: 99%
“…The curing reaction then runs according to the Equation (1). In contrast to traditional processes, the dehydration curing process of alkaline silicates results in significantly higher mechanical properties of molding mixtures, in this case determined as transverse strength, even at significantly lower binder dosages [8][9][10]. See the differences of transverse strength of molding mixtures using alkaline silicates binders cured by different methods in Figure 1, where the reference value 100% means the strength value for "microwave" curing (marked as MV) of molding mixture with inorganic binder and reaches transverse strength of approximately 4 MPa.…”
Section: Introductionmentioning
confidence: 99%